2024
DOI: 10.3389/fendo.2024.1330650
|View full text |Cite
|
Sign up to set email alerts
|

Normal triglyceride concentration and the risk of diabetes mellitus type 2 in the general population of China

Rubing Guo,
Lianhua Wei,
Yongtong Cao
et al.

Abstract: IntroductionHypertriglyceridemia and its derivatives are independent predictors of diabetes mellitus type 2 (T2DM). However, the relationship between triglyceride concentrations within the normal range and the incidence of T2DM remains to be clarified. This study investigated the potential relationship between variations in plasma triglyceride levels within the normal range and T2DM onset using data from a longitudinal study of health and retirement in China.MethodsBetween, 2010 and, 2016, we conducted a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…So far, only a few studies have explored the association between normal triglycerides and diabetes [14][15][16][17], and they have found that triglycerides in the upper normal range are positively associated with the prevalence [17] and new-onset of diabetes [14][15][16]. The current study expands our knowledge and found that triglycerides in the upper normal range were also associated with diabetes mortality.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…So far, only a few studies have explored the association between normal triglycerides and diabetes [14][15][16][17], and they have found that triglycerides in the upper normal range are positively associated with the prevalence [17] and new-onset of diabetes [14][15][16]. The current study expands our knowledge and found that triglycerides in the upper normal range were also associated with diabetes mortality.…”
Section: Discussionsupporting
confidence: 68%
“…To date, only a few studies have examined the relationship between triglycerides and diabetes in individuals with normal triglyceride levels [14][15][16][17]. Three independent studies discovered that higher normal triglycerides are associated with a higher risk of newonset type 2 diabetes in individuals from Israel [14], China [15], and the Netherlands [16]. Another study found a positive association between normal triglyceride levels and the prevalence of type 2 diabetes in Chinese adults [17].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown a positive relationship between triglycerides and diabetes prevalence [7] and incidence [26][27][28][29][30]. In addition, fibrates, triglyceride-lowering medications, protect against diabetes in both mice [31] and humans [32][33][34].…”
Section: Discussionmentioning
confidence: 99%